Pressures of jobseekers after graduation: Evidences from a public university of Bangladesh - Barman, Ram Proshad; Arifuzzaman Nishat; Hasan, Md. Rashidul (Goodwood Publishing, 2023)
Purpose: The goal of this study is to present the results for job seekers who have graduated from public universities. Methodology/approach: Quantitative and qualitative methods were used in this study. The data were gathered from 200 job-seeker students at Begum Rokeya University, Rangpur (BRUR), between February and May 2022. The study adopted a purposive sampling technique to select respondents and seven case studies to draw qualitative conclusions. The study also employed The chi-squared test was used to test the hypotheses.. Results/Findings: The results of the hypothesis are as follows: there is a strong relationship between economic crisis and highly salaried jobs ( ); a medium relationship between more time to complete graduation and the pressure on job career ( ); a medium relationship between lower preparation for a job and more participants than job capacity ( ); and finally, a medium relationship between cultural influence on respondents’ behavior and alienation from family and relatives ( ). This study also discovered that pressure on students comes from a variety of sources, including family, workplace, cultural hegemony, and academic pressure. Finally, the study concludes that students may reduce demands, the government can increase employment, and jobless youth may develop self-servicing possibilities for living. Limitations: The researchers had limitations because, even without these findings, the environment and appropriateness might be advantageous for graduates instead of pressures. Another barrier is time and money. Contribution: Students, job seekers, and society at large who are concerned about unemployment and the programs that may address it both domestically and internationally will find the research to be helpful.